DAIRY GOAT MILK AND COMPOSITION IN SO-CALLED DEVELOPING COUNTRIES - Orskov, Egil R. (2014)
Goat are generally kept on small farms and often in buildings beside the farmer's home. Many goat are used for milk production and goat milk is attracting prices up to 6 times the price per litre of cow milk. The main reason for this is that goat milk is very similar to human milk in many aspect of its composition and therefore more healthy for humans than cow milk. The fat content in goat milk is lower than that of cattle milk and the fat globules are smaller, making it more suitable for human consumption, particulary fo babies. it is argued in literature that the birth weights of humans and goat kids are similar 3.5kg-5kg. It is also shown that goat milk contains less lactose and cholesterol with more of Vitamin D and A and potassium, making the milk more alkaline. There are other differences too which make goat milk more suited to humans.